Motor learning in human movement science: a bibliometric analysis - Jiménez-Díaz, Judith (2025)
The increase in scientific production in various areas of human movement offers the opportunity to carry out bibliometric studies in the area of motor learning. The aim of the present study was to systematize the information published in the area of motor learning between the years 2000 and 2024 through a bibliometric analysis. Five-hundred seventy relevant studies on this subject, published between 2000 and 2024, were selected through a search in the Scopus database. An analysis of performance and structure metrics was carried out, taking into account publications, amount of documentation, annual growth rate of articles published, affiliations and most relevant authors, collaboration networks, those most quoted at a global level, thematic trends, and others. From the 570 documents analyzed, G. Wulf was identified as the most relevant author; the University of Toronto as the most relevant affiliation, and the United States of America as the country with the largest scientific production. The most quoted study addresses a topic related to the issue of degrees of freedom. In conclusion, this paper offers an overview of the scientific production in topics related to motor learning in the last 25 years.